Masalik al-Absar Fi Mamalik al-Amsar. - Ibn Fadl Allah al-'Umari's, Ahmad ibn Yahya, 1301-1349., author.
1 online resource (122 pages)
Keywords: Providing a modern English translation of a key selection of Ibn Fadl Allah al-`Umari's Masalik al-absar, this book offers a rich description of Egypt and Syria under the Mamluks in the first half of the fourteenth-century A.D. It provides a fascinating snapshot of the physical and administrative geography of this crucial region as well as insights into its society and the organization and functioning of the Mamluk state.